DMSO mimics inhibitory effect of thalidomide on choriocapillary endothelial cell proliferation in culture. Issue 11 (1st November 2002) - Eter, N; Spitznas, M
Abstract : Aim: To evaluate the effect of thalidomide on bovine choriocapillary endothelial cell proliferation. Methods: Posterior segments of bovine eyes were incubated with trypsin. After digestion of the tapetum, pieces of Bruch's membrane with the adherent choriocapillaris were scraped, digested again with a cocktail of enzymes, washed and cultured in MCDB 131 medium. Cells were incubated with 100 μg/ml thalidomide (dissolved in DMSO as recommended). Control cultures were incubated with DMSO alone or without any supplement. Cell proliferation after 24 hours was determined in a counting chamber. Purity of the cultures was controlled by immunohistochemical staining and labelling with low density lipoprotein. Results: Thalidomide dissolved in DMSO inhibited proliferation of choriocapillary endothelial cells compared to control cultures incubated without any supplement. However, DMSO alone suppressed cell proliferation equally well. Conclusion: In cultured bovine choriocapillary cells the inhibiting effect of thalidomide may at least in part be attributed to the solvent DMSO alone.